Immobilization of trypsin onto porous methacrylate-based monolith for flow-through protein digestion and its potential application to chiral separation using liquid chromatography. Issue 8 (August 2021) - Amalia, Suci; Angga, Stevin Carolius; Iftitah, Elvina Dhiaul; Septiana, Dias; Anggraeny, Baiq Octaviana D.; Warsito; Hasanah, Aliya Nur; Sabarudin, Akhmad
Abstract: Monolithic columns for analytical applications have attracted the researcher's attention. In this work, the laboratory-made organic-polymer monolithic column is modified with trypsin and further applied as a nanobiocatalyst microreactor and a stationary phase for separating chiral compounds by liquid chromatography. The monolith was synthesized by in-situ copolymerization of glycidyl methacrylate (GMA) and ethylene glycol dimethacrylate (EDMA) or trimethylolpropane trimethacrylate (TRIM) as a crosslinking agent, with porogen of 1, 4-butanediol/propanol/water (4:7:1 v/v) and AIBN as the radical polymerization initiator inside PEEK and silicosteel tubings (1.0 mm i.d × 100 mm) at 60 °C for 12 h. A total monomer ratio (%T) and crosslinking agent (%C) of 40:25 and 28:12 were applied to prepare poly-(GMA-co-EDMA) and poly-(GMA-co-TRIM), respectively. The produced monoliths were further modified by introducing trypsin (10 mg/L) through the ring-opening reaction of the epoxide group existing in the monolithic column. The trypsin-immobilized poly-(GMA-co-EDMA) monolithic column was applied as the nanobiocatalyst microreactor for online/flow-through and rapid digestion of β-casein sample into its peptide fragments. The trypsin-immobilized poly-(GMA-co-TRIM) column has potential application to be used as the HPLC stationary phase for the separation of R/S-citronellal enantiomers. Abstract : monolith, trypsin, HPLC, chiral stationary phase, microreactor